'You are a priest forever' : Second Temple Jewish messianism and the priestly christology of the Epistle to the Hebrews - Mason, Eric Farrel. (Studies on the Texts of the Desert of Judah, 2008)
Scholars have long questioned the conceptual background for the priestly Christology of the Epistle to the Hebrews, with suggestions including Gnosticism, the thought of Philo of Alexandria, common themes in early Christian theology and exegesis, and the creativity of the author of Hebrews himself. The discovery of the Dead Sea Scrolls prompted waves of enthusiasm for understanding Hebrews in that context, both in terms of the Qumran sect's priestly messianism and understanding of Melchizedek, but claims often were excessive and the approach was discredited. The present study reevaluates the priestly Christology of Hebrews and the presentations of the messianic priest and Melchizedek in the Qumran texts, arguing that the latter do indeed provide the closest parallels to Hebrews' thought.